A continuous contact force model for the impact analysis of hard and soft materials. (November 2022) - Zhang, Jie; Fang, Mingyang; Zhao, Lei; Zhao, Quanliang; Liang, Xu; He, Guangping
Highlights: A new continuous contact model is proposed with high accuracy. The new model can simulate impacts with remaining surface deformation after impact. The new model can simulate impacts with zero separation indentation. The model is verified by two published experimental data and typical contact models. Abstract: Impacts with remaining surface deformation or zero indentation at the separation time are common in mechanical systems with hard and soft materials, and corresponding contact force models have been established for these two types of collision phenomena, but there is a lack of models that can simulate both types of impacts. A new continuous contact model is proposed that can simulate these two types of collisions with high accuracy. By constructing an approximate equation, the new model is developed based on the typical equation of continuous contact models. Two published experiments related to two types of collisions are used for model validation; in addition, typical continuous models for the impact analysis of two types of collisions are utilized for the comparison. The validation and comparison show that the new model can simulate the impact with remaining surface deformation or zero separation indentation with high accuracy. The influences of the restitution coefficient and remaining surface deformation ratio on the system dynamic behaviors have also been investigated. The new model will be helpful for the dynamic simulation of mechanical systems with contact-impacts phenomena involving hard materials and soft materials.